Gypsies, the Roma and justice claims: the case of Lüleburgaz - Uzun, Begüm. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
The Gypsy/Roma communities in Europe have turned into an intense area of focus both at the international level and in academic circles in the last decade. In Turkey, the revival of interest with the Urban Regeneration projects that demolished the Roma settlements along with others in different parts of Turkey; the persistent references to the disadvantaged position of the Gypsy/Roma in Turkey in the EU progress reports and the increasing tendency of the Turkish Roma to get organized have also attracted considerable media and academic attention in the recent years in particular and have led to the increasing involvement of NGOs in the projects targeting the Gypsy/Roma communities in different parts of Turkey. In the light of these developments (which I call the “Europeanization of the Gypsy/Roma issue”), my thesis is an attempt to focus on a seriously understudied region of Turkey- the Kuştepe and Altıyol districts of Lüleburgaz (a town in the Thrace region in the northwest Turkey where a considerably large number of people defined as Gypsy/Roma by the majority population are living.).By utilizing data obtained through in-depth interviews, informal focus groups and participant observation in these districts, this research explores the current socioeconomic status of the residents of Altıyol and Kuştepe districts and how they perceive their own identity as well as how they respond/what kind of politics they entail to cope with their marginalization. I argue that the residents of Altıyol and Kuştepe districts constitute the local manifestation of racism towards the Gypsy/Roma in Turkey and thus should be identified as “a racialized group” in terms of their political, economic and social marginalization. What is striking, however, in the case of Lüleburgaz, is that the residents of the districts perceive being a Gypsy/Roma not as an ethnic affiliation but as a social/cultural and class position and develop ways to get rid of their perceived subaltern position. In this context, the main focus of my thesis is how the survival/coping strategies of the residents of Altıyol and Kuştepe districts have been replaced with their claims to justice. On the one hand, at the discursive level, by perceiving being a Gypsy/Roma as a subaltern position instead of ethnic affiliation and by sheltering strategically within the Islamic identity, I assert that their justice claims, at the discursive level, entail having access to employment, education, better housing and welfare benefits as equal Turkish citizens. On the other hand, however, that discursive strategy has been accompanied and somehow transformed at the action level by getting organized under Roma associations which are supposed to take action against the injustices towards them on the basis of Roma ethnic identity. In this sense, though conflicting and competing in nature with regard to citizenship, those justice claims are the strategies which strikingly reflect their increasing demands for integration with the larger society.
Keywords: Romanies -- Turkey -- Lüleburgaz.; Romanies -- Turkey -- Social conditions.